2020
DOI: 10.3390/ani10040664
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Characterization of Porcine Growing and In Vitro Matured Oocytes

Abstract: This study aimed to investigate ultrastructural changes of growing porcine oocytes and in vitro maturated oocytes. Light microscopy was used to characterize and localize the primordial, primary, secondary, and tertiary follicles. During oocyte growth and maturation, the morphology of mitochondria was roundish or ovoid in shape depending on the differentiation state, whereas their mean diameters oscillated between 0.5 and 0.7 µm, respectively, from primary and secondary follicles. Hooded mitochondria were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Besides their spatial and morphological heterogeneity in mature tissues, mitochondria are subjected to changes during tissue differentiation and maturation (Porter et al., 2011; Kere et al., 2020), as reviewed in Ding et al. (2021), Garbern & Lee (2021) for pluripotent stem cell‐derived cardiomyocytes.…”
Section: Cell Metabolism Correlates With Mitochondrial Morphodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides their spatial and morphological heterogeneity in mature tissues, mitochondria are subjected to changes during tissue differentiation and maturation (Porter et al., 2011; Kere et al., 2020), as reviewed in Ding et al. (2021), Garbern & Lee (2021) for pluripotent stem cell‐derived cardiomyocytes.…”
Section: Cell Metabolism Correlates With Mitochondrial Morphodynamicsmentioning
confidence: 99%
“…Besides their spatial and morphological heterogeneity in mature tissues, mitochondria are subjected to changes during tissue differentiation and maturation (Porter et al, 2011;Kere et al, 2020), as reviewed in Ding et al (2021), Garbern & Lee (2021) for pluripotent stem cell-derived cardiomyocytes. Although cardiomyocyte mitochondria are fragmented and clustered around the nucleus at early embryonic stage, they then become long and rod-shaped after 13.5 weeks.…”
Section: Cell Metabolism Regulates Mitochondrial Morphodynamicsmentioning
confidence: 99%
“…In pig oocytes, spherical mitochondria with few cristae are the main pattern of mitochondria observed before maturation, which presumably has only a low metabolic activity of energy [ 39 ]. Hooded mitochondria were rarely seen, in contrast to the more frequently existing shell-like and compartmentalized mitochondria in post-pubertal porcine oocytes [ 40 , 41 ]. A previous study reported that EMF might induce morphological changes in mitochondrial cristae in human pancreatic cancer cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%